y=-x-2

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=-(0)-2

Simplify -(0)-2.

Multiply -1 by 0.

y=0-2

Subtract 2 from 0.

y=-2

y=-2

Use the x and y values to form the ordered pair.

(0,-2)

(0,-2)

Remove parentheses.

y=-(1)-2

Simplify -(1)-2.

Multiply -1 by 1.

y=-1-2

Subtract 2 from -1.

y=-3

y=-3

Use the x and y values to form the ordered pair.

(1,-3)

(1,-3)

Remove parentheses.

y=-(2)-2

Simplify -(2)-2.

Multiply -1 by 2.

y=-2-2

Subtract 2 from -2.

y=-4

y=-4

Use the x and y values to form the ordered pair.

(2,-4)

(2,-4)

These are three possible solutions to the equation.

(0,-2),(1,-3),(2,-4)

Find Three Ordered Pair Solutions y=-x-2